2012
DOI: 10.4103/0976-237x.107424
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss, chewing ability and quality of life

Abstract: Objectives:The aim of this study was to observe the tooth loss over age in a sample of Brazilian patients and analyze their ability to chew, relating it to how much is the loss of oral function impact over the quality of life (QoL).Materials and Methods:This is a single center, observational study and the data were collected through clinical examination followed of questionnaires to obtain sociodemographic information, the ability to chew (through the index of chewing ability [ICA]) and QoL (through Oral Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
0
12

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 11 publications
4
55
0
12
Order By: Relevance
“…In line with these results, another study found a positive correlation between number of missing teeth and age (p <0.001) [10].…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In line with these results, another study found a positive correlation between number of missing teeth and age (p <0.001) [10].…”
Section: Discussionsupporting
confidence: 75%
“…As in this study, other studies had among volunteers a greater number of female participants [14,15], with low schooling [10,13] and low income [10]. Although female participants had higher QOL score (7.74) compared to males (6.09), the difference of impact on QOL between genders was not statistically significant (Mann-Whitney-Wilcoxon test, p = 0.304).…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…En pacientes adultos se encontró que una calidad de vida positiva está relacionada con la presencia de por lo menos 10 dientes en cada arcada, prefiriendo los dientes naturales Bortoluzzi et al;Jain et al;Sanders et al, 2009b;Zhang et al), además agrega que su disminución afectan la capacidad de masticar (Inukai et al), tendiendo un fuerte impacto negativo la pérdida total de dientes (Silva et al, 2010a). También en pacientes en los que se le realizó osteotomía de la mandíbula, debido a una mejora a los 2 meses de la estética, función, salud oral y satisfacción (Kavin et al), y en pacientes que recibieron una prótesis removible nueva (Hadzipasic-Nazdrajic).…”
Section: Discusionunclassified
“…Mientras que en otro estudio, el aumento de la capacidad de masticar se correlacionó con las puntuaciones más bajas OHIP y estuvo influenciado por el sexo, años de escolaridad, demanda de tratamiento y estado de los dientes (Inukai et al, 2010). En una población adulta brasileña se encontró que a medida que aumenta la edad (≥40 años) disminuye el número de dientes y la capacidad de masticar, generando un impacto negativo en la calidad de vida, afectando 5 de los 7 dominios: limitación funcional, dolor físico, bienestar psicológico, discapacidad física o psicoló-gica (Bortoluzzi et al, 2012). Así también, en otra población brasileña, a la misma edad y con necesidad de prótesis parcial y total declarada, se encontró un disminución en la calidad de vida (Miotto et al, 2012).…”
Section: Introduccionunclassified